Attachment representations among school-age children with intellectual disability. (November 2021) - Vanwalleghem, Stéphanie; Miljkovitch, Raphaële; Vinter, Annie
Highlights: School-age children with intellectual disability (ID) are at higher risk of disorganized attachment representations. Disorganized attachment representations are related to level of adaptive functioning. No differences were found in attachment representations between children with Down syndrome vs non-specific ID. Abstract: Background: Research data documenting a high risk of insecure and disorganized attachment among children with intellectual disability (ID) in infancy and early childhood raises the question of mutual influences between ID and attachment in later childhood. Aims: The objectives of the present study were to examine attachment among school-age children with ID and whether attachment varies according to level of intellectual functioning, adaptative functioning, and presence of a genetic syndrome (i.e. Down syndrome). Methods: Attachment among 54 children with ID aged 8−12 years (30 with Down Syndrome, 24 with non-specific ID) was assessed using the Attachment Story Completion Task, and compared with that of 108 typically developing children, 54 of the same chronological age and 54 of the same mental age. Outcomes: Results show (1) less security among children with ID than among same-age controls (2) more disorganization among children with ID compared to the two control groups, (3) a link between attachment disorganization and level of adaptive functioning among children with ID and (4) no difference in attachment between children with DS and children with non-specific ID. Conclusions: Children with ID remain vulnerable to disorganization during late childhood. More research is needed to understand the factors underlying disorganized attachment representations.